Overview of U.S. Department of Energy Office of Fossil Energy's Solid Oxide Fuel Cell Program. (30th May 2017) - Vora, Shailesh D; Lundberg, Wayne L.; Pierre, Joseph F.
Abstract : The U.S. Department of Energy Office of Fossil Energy (FE) National Energy Technology Laboratory (NETL) Solid Oxide Fuel Cell (SOFC) Program is committed to developing efficient, low-cost electricity from natural gas or coal with intrinsic carbon capture capabilities for distributed generation and central power generation applications; maintaining cell development and core technology research to increase the reliability, robustness, and durability of cell, stack, and system technology; and providing the technology base to permit cost-competitive distributed generation applications. Recent program efforts focused on addressing cell and system reliability (finding chromium contamination of the cathode a major contributor to performance degradation and reduced system reliability) and an Innovative Concepts initiative (developing novel cell and stack architectures and/or material sets). The status of these strategically oriented research programs, along with the status of the program's integrated systems tests and the roadmap to deploy a MWe-class natural gas-fueled distributed generation system, will be presented.